Minat Belajar Matematika dan Contextual Teaching And Learning bermuatan Etnomatematika Mbaru Tembong (Unika Santu Paulus Ruteng, 2023)
Interest in learning mathematics will encourage students to study mathematics. Therefore, interest in learning needs to be increased, one of which is with Contextual Teaching and Learning (CTL) with Mbaru Tembong ethnomathematics content. This study aims to describe the increased interest in learning mathematics in class IX E students at SMPN 4 Langke Rembong with the subject of curved side shapes, namely tubes and cones. To achieve this goal, cyclical learning is designed, each cycle starting with planning, implementing, observing and ending with reflection. The subjects in this study were 30 students in class IX E. The data collection technique used was the non-test technique in the form of a questionnaire of interest in learning and observation. The results showed an increase in students' learning interest in each cycle. The results of distributing questionnaires and observations made by researchers in the pre-action classical percentage were obtained in the high category of 6.6%. The percentage is classically determined by the high category, namely â‰¥75%. In cycle I, the percentage obtained from distributing questionnaires was in the high category, namely 13.3% and for the observation results, the average obtained was in the medium category. Because it was continued with planning with cycle II. In cycle II the classical percentage obtained was 93.3% and for the observations the average acquisition was in the high category. In cycle II, the percentage classically has reached the predetermined target so that the action is said to be successful. This shows that by applying Contextual Teaching and Learning (CTL) with Mbaru Tembong's ethnomathematics content, it can increase students' interest in class IX E at SMPN 4 Langke Rembong. Therefore, for teachers who want to increase students' interest in learning, one method that can be used is to apply Contextual Teaching and Learning (CTL) with ethnomathematics content. Students will feel that mathematics plays an important role in everyday life thereby increasing interest in learning mathematics